(untitled) (Global Journal of Science Frontier Research, 2023)
The characteristic graph of the atom makes it possible to explain the various concepts of atomics in a general way. Each concept is interpreted by specific graphics derived from the first. About the electronic structure, the particular graphs illustrating the order and the period of the subshells which obey the stability classify them in stacks according to the abscissas and the ordinates. The distribution of the electrons of the heaviest "118th" atom leads to new methods of illustrating classification called "condensed tables" with or without period and order subshells. The distribution of electrons according to the order of the energy level of the subshells denoted "OE," is based on a new criterion for the classification of chemical elements. This stems from arrays called condensed arrays to order. These condensed tables are summarized by numerical series whose informed reading makes it possible to explain the secrets of atomistic. The electronic structure can be worked out even by mental calculation. The counting from 1 to 7 or from 1 to 8 with the corresponding value series solves the development of the electronic structure. All the value series: 2, 8, 8, 18, 18, 32, 32, and 2, 2, 8, 8, 18, 18, 32, 30 made it possible to achieve this objective.